Updates in the Management of Hyperglycemic Crisis - Aldhaeefi, Mohammed; Aldardeer, Namareq F.; Alkhani, Nada; Alqarni, Shatha Mohammed; Alhammad, Abdullah M.; Alshaya, Abdulrahman I. (Frontiers in Clinical Diabetes and Healthcare, 2022)
Diabetes mellitus (DM) affects the metabolism of primary macronutrients such as proteins, fats, and carbohydrates. Due to the high prevalence of DM, emergency admissions for hyperglycemic crisis, diabetic ketoacidosis (DKA) and hyperglycemic hyperosmolar state (HHS) are fairly common and represent very challenging clinical management in practice. DKA and HHS are associated with high mortality rates if left not treated. The mortality rate for patients with DKA is < 1% and 15% for HHS. DKA and HHS have similar pathophysiology with some few differences. HHS pathophysiology is not fully understood. However, an absolute or relative effective insulin concentration reduction and increased in catecholamines, cortisol, glucagon, and growth hormones represent the mainstay behind DKA pathophysiology. Reviewing the patient’s history to identify and modify any modifiable precipitating factors is crucial to prevent future events. The aim of this review article is to provide a review of the DKA, and HHS management based on the most recently published evidence and to provide suggested management pathway of DKA of HHS management in practice.